Пінополіуретани з бар'єрними властивостями широкого спектра дії - Савельєв, Ю.В.; Марковська, Л.А.; Веселов, В.Я.; Савельєва, О.О.; Робота, Л.П.; Руденко, А.В.; Лебедєв, Є.В. (Видавничий дім "Академперіодика" НАН України, 2008)
New polyurthane foams of wide-activity spectrum (bactericidal, adhesive, and anesthetic) are synthesized. Formation conditions and some properties are presented. Such polyurethane may be used in medical practice for the creation of barrier-type polymers - temporary skin substitutes, bactericidal dressing material in wound and burns therapy, and transdermal therapeutic systems.